2022
DOI: 10.1049/hve2.12267
|View full text |Cite
|
Sign up to set email alerts
|

Application of an atmospheric pressure plasma jet in a rat model of ischaemic stroke: Design, optimisation, and characteristics

Abstract: Recent studies have shown the in vitro neuro-protective functions of atmospheric pressure plasma (APP) against multiple pathological injuries during ischaemic stroke (IS). However, whether APP treatment exerts a therapeutic effect on a rat IS model remains unclear. Here, on the basis of needle-to-ring dielectric barrier discharge, an atmospheric pressure plasma jet (APPJ) was designed, with the Helium as the working gas which was driven by a sinusoidal voltage. Then, the treatment conditions were optimised for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Another study reported that atmospheric pressure plasma jets (APPJ) could reduce the damage of middle cerebral artery occlusion and improve neurological function. Plasma-induced NO generation could be potentially used as a cytoprotective agent 22 . On the other hand, previous studies have reported that CAP could notably stimulate the differentiation of neuronal stem cells and promote increased neuronal regeneration following trauma [23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that atmospheric pressure plasma jets (APPJ) could reduce the damage of middle cerebral artery occlusion and improve neurological function. Plasma-induced NO generation could be potentially used as a cytoprotective agent 22 . On the other hand, previous studies have reported that CAP could notably stimulate the differentiation of neuronal stem cells and promote increased neuronal regeneration following trauma [23][24] .…”
Section: Introductionmentioning
confidence: 99%